Can sexual transmission support the enzootic cycle of Trypanosoma cruzi? - Rios, Adriano (2018)
BACKGROUND Trypanosoma cruzi circulates in sylvatic habitats, mainly through blood-feeding triatomines, although other routes also contribute to its dispersion. Sexual transmission of T. cruzi is an understudied topic, especially among wild mammals. Because of the difficulties inherent to field work, experimentally infected mice are frequently used to evaluate the transmission of T. cruzi. OBJECTIVE This study aimed to evaluate the sexual transmission of T. cruzi in acutely infected mice. METHODS Male and female mice in the acute phase of Chagas disease were mated with naïve partners. Then, parasitological tests, immunohistochemistry, serological assays, and polymerase chain reaction (PCR) assays were used to detect infection. FINDINGS Parasitological analysis showed trypomastigotes in the blood of 20% of the naïve mice after mating with infected partners. Serological assays detected anti-T. cruzi antibodies in all naïve females mated with infected males and in 60% of naïve males mated with infected females. PCR showed T. cruzi nDNA bands for all naïve mice mated with infected partners. The possibility of sexual transmission was also confirmed by visualisation of amastigotes in the testes. MAIN CONCLUSIONS Our results demonstrate that sexual transmission of T. cruzi is an ordinary event that may contribute to maintenance of the parasite's enzootic cycle.